2016
DOI: 10.1021/acs.biomac.6b00129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Noncellulosic Compounds on the Nanoscale Interaction Forces Measured between Carbohydrate-Binding Module and Lignocellulosic Biomass

Abstract: The lack of fundamental understanding of the types of forces that govern how cellulose-degrading enzymes interact with cellulosic and noncellulosic components of lignocellulosic surfaces limits the design of new strategies for efficient conversion of biomass to bioethanol. In a step to improve our fundamental understanding of such interactions, nanoscale forces acting between a model cellulase-a carbohydrate-binding module (CBM) of cellobiohydrolase I (CBH I)-and a set of lignocellulosic substrates with contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…The fact that no rupture forces greater than 25 pN were measured for Y67A at 1 pN/s could be related to the difference in sample size (N=259 vs. N=138 for WT and Y67A, respectively) as the tail of larger rupture forces at 0.1 pN/s is similar for WT and Y67A (N=161 vs N=159 for WT and Y67A, respectively). A similar shape of rupture force distributions was observed in previous AFM-based studies for CBM3a (27) and CBM1 (24, 56) but previous AFM analysis showed a more Gaussian-like distribution for CBM3a (28), (25). King et al (27) showed that specific binding of CBM3a can be blocked with the addition of NCC and restored by washing the CBM-functionalized AFM tip with an excess of water.…”
Section: Discussionsupporting
confidence: 86%
“…The fact that no rupture forces greater than 25 pN were measured for Y67A at 1 pN/s could be related to the difference in sample size (N=259 vs. N=138 for WT and Y67A, respectively) as the tail of larger rupture forces at 0.1 pN/s is similar for WT and Y67A (N=161 vs N=159 for WT and Y67A, respectively). A similar shape of rupture force distributions was observed in previous AFM-based studies for CBM3a (27) and CBM1 (24, 56) but previous AFM analysis showed a more Gaussian-like distribution for CBM3a (28), (25). King et al (27) showed that specific binding of CBM3a can be blocked with the addition of NCC and restored by washing the CBM-functionalized AFM tip with an excess of water.…”
Section: Discussionsupporting
confidence: 86%
“…The exceptions are the studies of Guo and Arslan. They studied the affinities of Tr CBM1 to various cellulose substrates 25 as well as the binding behavior of Tr CBM1 to lignocellulosic substrates using an atomic force microscope 26 . These reports described the expression and purification of Tr CBM1.…”
Section: Discussionmentioning
confidence: 99%
“…AFM provides a valuable approach to quantify interactions between biomolecules [52]. AFM’s ability to quantify biomolecular forces with pico-newton resolution in liquid environments [47, 57] allowed researchers to investigate protein-ligand [58], protein-DNA [59], protein-protein [60], and protein-biomolecule [61] interactions at the nanoscale. The ability to work with full-length proteins, the use of relatively low protein concentrations (~0.5 to 3 μM in this study) and stability of actin in a monomeric form make AFM a promising technique for measuring forces of interaction of G-actin with other actin-nucleating and actin-sequestering proteins.…”
Section: Discussionmentioning
confidence: 99%